THE EFFECT OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) THERAPY ON DEPRESSION LEVELS IN THE ELDERLY - Nurul Hemmawati (Perhimpunan Kesehatan Holistik Indonesia, 2020)
Depression is a feeling of sadness and pessimism associated with an affliction. Depression is a mental health problem which most commonly occurs in the elderly. Elderly with depression are had a higher risk of suicide. Based on the survey of July until October 2014 found that 7 of 10 elderly with depression. It show the high incidence of depression in the elderly in UPT Panti Sosial Lanjut Usia Blitar Tulungagung 2015. The purpose of this study was to determine the effect of SEFT therapy for depression level in the elderly. This research use pre-experiment design, with one group pre-post test design. Data source of this research is the primary data. Total population was 18 people and the 15 people selected to be the subject by purposive sampling. The independent variable of this study is SEFT therapy and the dependent variable is the depression level in the elderly. The results of this research was there were some differences of depression level before and after give SEFT therapy. Before SEFT therapy, the level of mild depression about 46.7% and middle level depression was 53.3% then after give SEFT therapy mild level depression is about 86.7% and middle level depressin is 13.3%. The data were analyzed with statistical test by Wilcoxon test. P value 0.001 obtained depressed levels, then H0 is rejected and H1 is accepted. There are differences in the level of depression before and after given SEFT therapy in elderly SEFT in UPT Panti Sosial Lanjut Usia Blitar Tulungagung 2015. Thus, respondents expected SEFT therapy as a non-pharmacological therapy for depression.